Studies on Schismatoglottideae (Araceae) of Borneo XXXXVI: Fenestratarum mulyadii–A second species for a recently described genus - Boyce, P.C; Wong, Sin Yeng (International Aroid Society, Inc., 2015)
A second species of the recently established genus Fenestratarum is described, from Kalimantan Timur, Indonesian Borneo, as Fenestratarum mulyadii. This new species represents an over 600 km eastwards extension to the known range of the genus. Fenestratarum mulyadii is figured in colour, and compared to